Distribution, Abundance, and Biomass of Tropical Limpet Cellana testudinaria (Class: Gastropoda, Family: Patellidae) Living on the Rocky Shore of Ohoiwait, Southeast Moluccas, Indonesia - Abraham Samuel Khouw (Marine Science Department Diponegoro University, 2006)
Distribusi, kelimpahan, dan biomassa dari limpet C. testudinaria digambarkan secara terpisah untuk zona pantai bagian atas, tengah, dan bawah. Total 2402 ekor limpet diperoleh selama 12 bulan (dari Oktober 2001 sampai 2002). Rata-rata densitas adalah 11.12 ± 4.51 ind.m-2. Densitas tertinggi berada pada zona atas dan tengah daripada zona bawah. Analisa varian menunjukkan perbedaan nyata antar zona, bulan, dan interaksi zona-bulan. Pola penyebaran limpet adalah berkelompok. Rata-rata biomass tahunan diestimasi sebesar 1013± 748 mg AFDW.m-2 (21.8 kJ.m-2). Biomassa tertinggi 3236 mg AFDW.m-2 atau 69.9 kJ.m-2 ditemukan pada bulan September 2002, sementara terrendah pada bulan Maret 2002 sebesar 544 mg AFDW.m-2 atau 11.7 kJ.m-2. Rata-rata biomassa pada musim hujan 619 mg AFDW.m-2 atau 13.4 kJ.m-2 lebih rendah dibandingkan pada musim kemarau yakni 899 mg AFDW.m-2 atau 19.4 kJ.m-2.Kata kunci: Limpet, Cellana testudinaria, distribusi, kelimpahan, biomassa The distribution, abundance, and biomass of the tropical limpet C. testudinaria are described separately for the high, middle and low shore levels. A total of 2402 limpets were obtained in 12 monthly collections (from October 2001 to September 2002). The mean density over the whole period was 11.12 ± 4.51 ind.m-2. The density tended to be higher at the high (15.79 ± 7.54 ind.m-2) and the middle (14.67 ± 13.99 ind.m-2) than at the low shore level (2.90 ± 2.44 ind.m-2). Analysis of variance showed significant density differences among shore levels, months, as well as a significant interaction between shore levels and months. The smallscale dispersion patterns did not show any seasonal variability. They were strongly clumped throughout the year and at each shore level. The mean annual population biomass was estimated to be 1013 ± 748 mg AFDW.m-2 (21.8 kJ.m-2). The highest biomass (3236 mg AFDW.m-2 or 69.9 kJ.m-2) occurred in September 2002, whilst the lowest (544 mg AFDW.m-2 or 11.7 kJ.m-2) was in March 2002. The monthly mean biomass (619 mg AFDW.m-2 or 13.4 kJ.m-2) of the rainy season was lower than that (899 mg AFDW.m-2 or 19.4 kJ.m-2) of the dry season.Key words: Limpet, Cellana testudinaria, distribution, abundance, biomass